Contamination of Escherichia coli in Orange Juice in Angkringan Tourism Area, Malioboro Area, Yogyakarta - Dyah Suryani; Wibowo Wibowo (Health Notions, 2018)
Background: Orange juice is a popular drink in terms of taste, aroma, and price. However, if the behavior of the drink handler and environmental hygiene sanitation does not meet the requirements, it will allow the beverage to be contaminated with E. coli bacteria which can cause health problems. This study aimed to examine the relationship between behavior and angkringan sanitation with the existence of E. coli bacteria on orange juice in angkringan around Malioboro area of Yogyakarta City. Methods: This was observational analytic study with cross sectional time frame. The research samples were the angkringan reseller in Malioboro Region, amounting to 40 samples, 40 samples of orange juice and 40 samples of ice cubes. Data analysis used univariate analysis and bivariate analysis with Fisher statistical test. Results: The results of univariate analysis showed the good behavior of drink handler by 60%, good sanitation angkringan as much as 52.5%, 75% of ice cubes and 80% of the qualified or was found negative based on laboratory test in orange juice. The result of bivariate analysis, there was a relationship between the behavior of the drink handler with the presence of E. coli p = 0.042. There was no relationship between sanitation angkringan with the presence of E. coli p = 0.442. There was no relationship between the presence of E. coli on ice cubes and E. coli in orange ice p-value = 0.089. Conclusion: There was no correlation between sanitation of angkringan and the presence of E. coli on ice cubes and E. coli on orange juice. There was a relationship between the behavior of the beverage processor and the presence of E. coli on orange juice. Keywords: E. coli, Behavior, Sanitation of angkringan